Hypouricaemia and increased renal urate clearance associated with hyperparathyroidism. - Gibson, T (1976)
A 64-year-old female was found to have hypouricaemia, with serum uric acid ranging from 0.06-0.12 mmol/l (1.1-2.0 mg/100 ml), associated with an increased urate clearance of 48.9 ml/min and hyperparathyroidism. Known causes of increased uric acid clearance were excluded. Pyrazinamide reduced urate clearance dramatically to 2.1 ml/min, suggesting that the tubular defect was either one of increased secretion or a failure of postsecretory reabsorption. No other tubular abnormality was apparent except diminished urine concentrating ability. Hypouricaemia has not been previously reported in association with hyperparathyroidism and a mechanism relating the two disorders could not be readily postulated. The tubular defect shown in this instance resembled that reported in association with Wilson's disease and Hodgkin's disease. This case and earlier reports of isolated tubular defects of uric acid handling enhance our understanding of uric acid excretion.